(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article highlights the problem of the absence of an inclusive environment for people with disabilities as a factor in the declarative nature of inclusive reforms. Actual barriers and problems that prevent people with disabilities from participating actively in society are described. These barriers require an integrated approach to develop practical solution and minimize them. Pedagogical aspect of terms "inclusion" and "inclusive environment" is the most developed (right now). Nevertheless, the main idea of the pedagogical concept of inclusion is the creation of a "school for all" that meets the common European standards and the mission of creating a society for all. So the idea of inclusivity at this point has a broader meaning than simply creating the right environment at school. The key elements of social and pedagogical aspects are recognition of diversity, elimination of inequalities, minimization of barriers and creation of conditions in which any exclusion in all spheres of life is impossible. Psychological aspect of inclusion is to understand psychological well-being as an important element of it. Psychological conditions of an inclusive environment should contribute to the individual’s experience of subjective well-being. Based on the etymology of the word, you can describe inclusion as the process of forming a single whole by combining different parts. Having analyzed the social, pedagogical and psychological aspects of defining this concept, we believe that it is only whole environment in which inclusion must be realized. Thus, an inclusive environment is a human environment that provides conditions for inclusion of all persons into the spheres of society through the elimination of any barriers, taking into account the diversity of people. The integrated concept gives the opportunity to scientifically substantiate the design of new projects, programs and creation of inclusive social services.